2018
DOI: 10.15640/ijgws.v6n2a1
|View full text |Cite
|
Sign up to set email alerts
|

Western Beauty Pressures and Their Impact on Young University Women

Abstract: This research examines the impact of Western beauty pressures on a select group of young Canadian women. I gathered data using qualitative semi-structured interviews and analysed the data using an intersectional analysis of oppression in order to learn how women"s race, class and culture backgrounds shape their experiences with Western beauty pressures. The interviews were analysed using the voice-centred relational method of data analysis. The thirteen women interviewed discussed their perceptions of Western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…As a result, the self-worth and education of many young women of color are negatively impacted. For high school girls, this is especially true because they are becoming more interested in how they look, particularly how they look in the eyes of their peers (Mckay, 2014). An attractive physical appearance becomes increasingly important and is often equated with being "perfect".…”
Section: Self-worthmentioning
confidence: 99%
See 4 more Smart Citations
“…As a result, the self-worth and education of many young women of color are negatively impacted. For high school girls, this is especially true because they are becoming more interested in how they look, particularly how they look in the eyes of their peers (Mckay, 2014). An attractive physical appearance becomes increasingly important and is often equated with being "perfect".…”
Section: Self-worthmentioning
confidence: 99%
“…Interestingly, the researchers also found that as the amount of time used to achieve advertised perception of beauty and perfection increases, these students' interest in academic success decreased. (2006) In relation to gender roles and beauty, Mckay (2014) found that being a female athlete while trying to meet Western standards of idealized femininity was problematic. Since sports are typically considered to be a male domain, women who enter this space are often ridiculed, masculinized and harassed.…”
Section: Media Use and Perceptions Self-worthmentioning
confidence: 99%
See 3 more Smart Citations